The storyteller's voice: The dialogic art of Elizabeth Gaskell. - Hauch, Linda A. (University of Ottawa (Canada), 1991)
Elizabeth Gaskell was a gifted storyteller. Her letters and her fiction attest to an imagination rooted in oral narrative, marked by the digressiveness and dispersiveness of living speech. She wrote her first novel, she said, as if she were "speaking to a friend over the fire on a winter's night," and the dynamic of telling and listening, the model of the oral narrative act, is paradigmatic of her own narrative. The incorporation of a listener's response into the telling of her story has both formal and semantic implications in Gaskell's fiction. It leads to what one critic has called that "congenial shapelessness of a voice expecting at any moment to be interrupted," and as such it can account, in part, for the shapelessness that has traditionally been deemed a formal weakness in Gaskell's art. As she tells her stories in anticipation of the active, often resistant, response of her listener, the stories take shape accordingly, and traditional norms of narrative with their notions of unity, shapeliness and authorial control must be reconsidered. Gaskell's approach stresses the dynamic of varying, often conflicting, voices in relationship with one another, suggesting her view of language and narrative as active agents in a process of exchange and contestation which calls for a redefinition of the nature of meaning in narrative. The shaping activity that occurs as voices come in contact with and question one another shows meaning to be produced through an open movement of relationship and response, not predetermined by finalized definitions; it is constituted through the transforming act of telling and listening. (Abstract shortened by UMI.)
Keywords: Literature, English.